A puzzle about the fixity of the past. (23rd April 2022) - Lampert, Fabio
Abstract: It is a widely held principle that no one is able to do something that would require the past to have been different from how it actually is. This principle of the fixity of the past has been presented in numerous ways, playing a crucial role in arguments for logical and theological fatalism, and for the incompatibility of causal determinism and the ability to do otherwise. I will argue that, assuming bivalence, this principle is in conflict with standard views about knowledge and the semantics for 'actually'. I also consider many possible responses to the argument.